Discovery of second new species of the genus Spiniphilus Lin & Bi, and female of Heterophilus scabricollis Pu with its biological notes (Coleoptera: Vesperidae: Philinae: Philini) - Bi, Wenxuan; Lin, Meiying (Zootaxa, 2015)
A new philine species of the genus Spiniphilus Lin & Bi, 2011, S. xiaodongi sp. nov. is described from Yunnan, China. The female of Heterophilus scabricollis Pu, 1988 is described for the first time with its biological and ecological data.